Synthesis, Absolute Configuration, Biological Profile and Antiproliferative Activity of New 3,5-Disubstituted Hydantoins - Mladenka Jurin; Ana Čikoš; Višnja Stepanić; Marcin Górecki; Gennaro Pescitelli; Darko Kontrec; Andreja Jakas; Tonko Dražić; Marin Roje (MDPI AG, 2024)
Hydantoins, a class of five-membered heterocyclic compounds, exhibit diverse biological activities. The aim of this study was to synthesize and characterize a series of novel 3,5-disubstituted hydantoins and to investigate their antiproliferative activity against human cancer cell lines. The new hydantoin derivatives 5a-i were prepared as racemic mixtures of syn- and anti-isomers via a base-assisted intramolecular amidolysis of C-3 functionalized β-lactams. The enantiomers of syn-5a and anti-hydantoins 5b were separated by preparative high-performance liquid chromatography (HPLC) using n-hexane/2-propanol (90/10, v/v) as the mobile phase. The absolute configuration of the four allyl hydantoin enantiomers 5a was assigned based on a comparison of the experimental electronic circular dichroism (ECD) and vibrational circular dichroism (VCD) spectra with those calculated using density functional theory (DFT). The antiproliferative activity evaluated in vitro against three different human cancer cell lines: HepG2 (liver hepatocellular carcinoma), A2780 (ovarian carcinoma), and MCF7 (breast adenocarcinoma), and on the non-tumor cell line HFF1 (normal human foreskin fibroblasts) using the MTT cell proliferation assay. In silico drug-like properties and ADMET profiles were estimated using the ADMET Predictor ver. 9.5 and the online server admetSAR. Eighteen new 3,5-disubstituted hydantoins were synthesized and characterized. The compound anti-5c showed potent cytotoxic activity against the human tumor cell line MCF7 (IC50 = 4.5 µmol/L) and the non-tumor cell line HFF1 (IC50 = 12.0 µmol/L). In silico analyzes revealed that the compounds exhibited moderate water solubility and membrane permeability and are likely substrates for CYP3A4 and P-glycoprotein and have a high probability of antiarthritic activity.